Pengembangan Ekowisata Hutan Mangrove Pantai Baros Desa Titihargo Kecamatan Kretek Kabupaten Bantul - Hesti Purwaningrum (Journal of Tourism and Economic, 2020)
A research about "the Development of Ecotourism Baros Mangrove Forest, Titihargo, Kretek, Bantul”, has been carried in 2019. Baros Mangrove Forest Ecotourism Area, a tourist destination which was pioneered since 2003 by an NGO and local community. At present the management is carried out by local people from the elements of several Working Groups in Tirtohargo who joined KP2B (Baros Youth Group). This research uses a qualitative method whose technical implementation is carried out by literature review, interview and observation. The type of data obtained are primary data and secondary data. The observed variables are biogeophysical, socioeconomic and human resources. The results of the study show the Baros Manggrove Forest Area as a tourist destination has not maximized its management with the principle of ecotourism. Baros Mangrove Forest Ecotourism Development has a positive impact on the surrounding community. KP2B as the manager develops the Baros Mangrove Forest Area as an ecotourism with four activities namely conservation, education, social and economy.